ALA photodynamic therapy combined with dual 980nm/1470nm diode laser for classic Kaposi's sarcoma - Yajing Cao; Dixin Wang; Yeqiang Liu; Linglin Zhang; Xiuli Wang (Photodiagnosis and Photodynamic Therapy)
A 84-year old man who has a history of refractory Kaposi's sarcoma (KS) was treated with ALA-PDT combined with the dual 980-nm/1470-nm diode laser for 6 times every other week. Satisfactory result was noted without any unbearable adverse effects. The combination of the dual 980nm/1470 nm diode laser and ALA-PDT may be astrategy in treating local KS with good tolerance, especially in elder patients who can not tolerate radiotherapy and chemotherapy.